DISCHARGE APPARATUS - ARAKI KAZUHIRO; MATSUKURA KIYOSHI (1991)
PURPOSE:To dispense with a molded product for fixing by fixing strip-shaped discharge electrodes having a large number of small holes formed thereto at equal intervals in the longitudinal direction by inserting wire like electrode wire through the small boles of the discharge electrodes on one end side thereof and connecting springs to the small holes on the other end side of said electrodes to provide the discharge electrodes under tension. CONSTITUTION:In a discharge apparatus consisting of discharge electrodes 1 and the opposed electrodes 2 opposed to said discharge electrodes 1, a large number of small holes 10 are formed to the strip-shaped discharge electrodes 1 at equal intervals in the longitudinal direction thereof. The discharge electrodes 10 are fixed to the mounting parts 31 of a fixing frame 3 by inserting a wirelike electrode wire 4 through the small holes 10 on one end side of the discharge electrodes 1 and pulling force applying springs 35 are connected to the small holes 10 on the other end side of said electrodes 1 to fix the discharge electrodes 1 to the mounting parts 32 of the fixing frame 3 under tension. As a result, disconnection due to consumption accompanying discharge is eliminated and the molded product for fixing the discharge electrodes is unnecessary and manufacturing cost is reduced and mounting also becomes easy.